Obra total. Wpływ twórczości Cesara Manrique na krajobraz przyrodniczo-architektoniczny Lanzarote - Szulc, Magdalena (Studia Europaea Gnesnensia, 2023)
This paper discusses the oeuvre of the Spanish artist Cesar Manrique, who lived and worked in Lanzarote from the 1970s until his death in 1992. His versatile art (the artist created buildings, sculptures, paintings, prints and other art forms) changed the island’s appearance and the attitude of its inhabitants towards the landscape and the fusion of nature and architecture. Manrique’s work was innovative and continues to inspire architects, sculptors and painters today. The aim of this article is to outline selected examples of the solutions proposed by Manrique and their impact on the notions of how nature can be combined with architecture.